Effects of surfactant treatment in late preterm infants with respiratory distress syndrome. (19th May 2018) - Dani, Carlo; Mosca, Fabio; Vento, Giovanni; Tagliabue, Paolo; Picone, Simonetta; Lista, Gianluca; Fanos, Vassilios; Pratesi, Simone; Boni, Luca
Abstract: Objective: To evaluate surfactant effectiveness for the treatment of respiratory distress syndrome (RDS) in late preterm infants. Methods: We performed a retrospective cohort study of infants born between 34 +0 and 36 +6  weeks of gestation admitted for respiratory failure in seven perinatal centers from January 2010 to December 2014. We evaluated changes of FiO2, PaO2 and a/APO2 in surfactant-treated patients, and the need and duration of MV, the duration of noninvasive respiratory support, stay in NICU and in hospital in surfactant-treated and untreated late preterm infants with RDS alone. Results: We studied 562 infants with RDS, 252 (45%) were treated with surfactant and 310 (55%) were not. FiO2, PaO2 and a/APO2 significantly improved after surfactant treatment. The adjusted odds ratio for the need of MV and the adjusted differences of duration of noninvasive respiratory support, and of NICU and hospital stay were not different in the surfactant and non-surfactant groups. Conclusions: Surfactant therapy was followed by a quick and persisting significant improvement of respiratory function in late preterm infants with RDS. Surfactant did not improve short-term outcomes in our population probably because other factors such as the gestational age, occurrence of complications and poor feeding play a relevant role.